(untitled) (The Research of Medical Science Review, 2025)
This prospective observational study analyzes functional outcomes and satisfaction scores among patients receiving conservative treatment for midshaft clavicle fractures (MCFs) in a Karachi, Pakistan, tertiary trauma center. Employing analysis via SPSS-based, the investigation assesses how demographic predictors and comorbidities influence patient-reported satisfaction using the Disability of the Arm, Shoulder and Hand (DASH) scoring system. Among 110 patients, 58.7% were improved, and dissatisfaction was positively related to old age and the conditions of diabetes mellitus and hypertension. The results emphasize the unfulfilled expectations of conservative management in targeted subpopulations and demand evidence-based risk stratification. The findings contribute regional data to the worldwide orthopedic literature and promote a more informed approach to the treatment of MCFs in low-resource groups